0032 Building capacity among local health departments to disseminate naloxone to community members in north carolina. (26th April 2015) - Sachdeva, Nidhi; Bryson, Amy; Massey, Joy; Zuskov, Diana; Moore, Elizabeth; Soora, Shriya; Proescholdbell, Scott
Abstract : Statement of purpose: Over 1, 000 people each year die from drug overdose in North Carolina. Naloxone can effectively reverse an opioid overdose. Community access to naloxone has increasingly become a standard overdose prevention strategy. In 2013, North Carolina passed a Good Samaritan/Naloxone Access law intended to increase access to naloxone by those at risk, community, and family members. The use of standing orders for naloxone among Local Health Departments (LHDs) may be an effective distribution mechanism for the state. However, to date, it is unclear which LHDs have standing orders in place and which need further technical assistance. Methods/Approach: North Carolina Division of Public Health teamed with University of North Carolina Gillings School of Global Public Health graduate students to assess the statewide implementation of standing orders and the need for additional technical assistance to LHDs. Using mixed methods, the team combined survey results and key informant interviews to document standing order procedures, collect resources, analyse lessons learned and create a tailored dissemination plan to assist LHDs in establishing standing orders for naloxone distribution. Results: Key informant interviews are ongoing. A survey of LHDs has been launched and data collected. However, based on historical results, the survey response rate should be over 80% of the 87 LHDs based in NC. Toolkit development is in progress with plans to finalise and distribute mid-2015. Conclusions: Drug overdose continues to plague many areas. North Carolina successfully passed legislation in 2013 that would expand the use of naloxone (opioid antidote) by communities, friends and families. LHDs play a critical role in disseminating naloxone to the community to help prevent and reduce additional mortality and morbidity. Significance and contribution to the field: Understanding the implementation of overdose prevention strategies at the local level is critical to preventing future deaths. Despite the passage of a naloxone bill, it was unclear to what extent LHDs were able to successfully implement standing orders and provide naloxone to those who might be at risk. Developing a toolkit for LHDs and tailored dissemination plan was essential to this project and to building local capacity for naloxone distribution.